Knowledge, attitude and practice on workplace safety awareness among government agencies in Kota Bharu, Kelantan - Abedinlah, Amirah (Universiti Sains Malaysia, 2012)
A study was conducted among government agencies in Kota Bharu to assess the level of knowledge, attitude and practice on workplace safety awareness. A random sampling was used for the study and 260 participants were involved in this study. The questionnaires were distributed to the employer's representative and employee's representative. The mean age of the participants was 40 years with a standard deviation of 1 0.51. The participants who participated in this study had high level of knowledge, 85.1 percent (mean= 29.46, SD = 3.61), positive level of attitude 67.6 percent (mean= 40.04, SD = 5.15) and good level of practice, 50.9 percent (mean = 25.92, SD = 4.55). Significant associations were found between training and practice (p< 0.001), knowledge and practice (p=0.05) and attitude and practice (p=0.05). This findings study indicates that if people are given the training about the workplace safety, they may eventually have good practice in safety in the workplace. And also if they had high level of knowledge and positive attitude, they will practice what they know in prevent the accident at workplace.